2010
DOI: 10.2322/tastj.8.pc_59
|View full text |Cite
|
Sign up to set email alerts
|

Models of Membrane Space Structures with Inflatable Tubes

Abstract: Three models of deployable membrane space structures consisting of a membrane, inflatable tubes, and connective cable networks are investigated with the aim of developing suitable modules for future hierarchical modular space structure systems on a scale of hundreds of meters. To a flat spirally folded membrane, inflatable tubes are attached in the circumferential direction, the radial direction, or both. Deployment experiments on laboratory-scale hand-made conceptual models are carried out, and their details … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The thickness of the material, for example, often causes issues (ex. wrinkling, local buckling) during the coiling process [14,17,19,20], while alternate wrapping methods have been suggested that accommodate thickness [21][22][23]; these methods do not include a sealed inner volume and thus are not suitable for pneumatic actuator use.…”
Section: Party Horns and Coiled Inflatable Boomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the material, for example, often causes issues (ex. wrinkling, local buckling) during the coiling process [14,17,19,20], while alternate wrapping methods have been suggested that accommodate thickness [21][22][23]; these methods do not include a sealed inner volume and thus are not suitable for pneumatic actuator use.…”
Section: Party Horns and Coiled Inflatable Boomsmentioning
confidence: 99%
“…The dynamics and geometry of inflatable booms during deployment have been studied and simulated by [24][25][26][27][28]. Results have found that the deploying motion can be unstable, unpredictable, chaotic, and even catastrophic [15,20,27], particularly in an orbital environment. Researchers have tried to address this by using hook-and-loop strips [29], adhesive [26], and flexible plates [30] as methods to slow down deployment.…”
Section: Party Horns and Coiled Inflatable Boomsmentioning
confidence: 99%
“…In the 'coiled' configuration the inflation gas enters at the base of the boom and, as the boom is inflated, the coiled section is pushed along and unfurls. In the 'wrapped' configuration the gas enters from the hub, and the stowed boom swings out from the base during inflation; this configuration was used by Katsumata et al [14] for embedding inflated booms in a wrapped membrane.…”
Section: A Coiling and Wrappingmentioning
confidence: 99%